Revealing Spider Silk's 3D Nanostructure Through Low Temperature Plasma Etching and Advanced Low-Voltage SEM - Stehling, Nicola; Abrams, Kerry J.; Holland, Chris; Rodenburg, Cornelia (Frontiers in Materials, 2019)
The excellent mechanical properties of spider dragline silk are closely linked with its multiscale hierarchical structuring which develops as it is spun. If this is to be understood and mimicked, multiscale models must emerge which effectively bridge the length scale. This study aims to contribute to this goal by exposing structures within Nephila dragline silk using low-temperature plasma etching and advanced low voltage scanning electron microscopy. It is shown that secondary electron hyperspectral imaging (SEHI) is sensitive to compositional differences on both the micro and nano scale. On larger scales it can distinguish the lipids of the skin from the protein core, while at smaller scales SEHI is effective in better resolving nanostructures present in the matrix. Key results suggest that the silks spun at lower reeling speeds tend to have a greater proportion of smaller nanostructures in closer proximity to one-another in the fiber, which we associate with the fiber’s higher toughness but lower stiffness. The bimodal size distribution of ordered domains, their radial distribution, nanoscale spacings and crucially their interactions may be key in bridging the length scale gaps for current spider silk structure property models and successful biomimetic implementation.